Father-Child Playfulness: A Secondary Analysis of a Multiple-Baseline Single-Subject Study of Three Children With Autism Spectrum Disorder - Waldman-Levi, Amiya; Kuhaneck, Heather (The American journal of occupational therapy, 2023)
Ayres Sensory Integration® (ASI) is commonly used with children on the autism spectrum to promote sensory processing and improved occupational performance, including play. To date, there has been no explicit effort to examine improvements in playfulness through ASI. To explore whether ASI, coupled with parent training, improves child playfulness and fathers' support of child playfulness. Single-subject A-B-BC design secondary analysis of a nonconcurrent multiple-baseline study. Occupational therapy clinic. Three father-child dyads; children were ages 3 to 6 yr, with autism spectrum disorder (ASD) and documented sensory processing concerns. After a baseline phase, each child received at least 24 sessions of ASI, and fathers received parent training focusing on sensory processing issues and play via an online presentation. The Parent/Caregiver's Support of Children's Playfulness and the Test of Playfulness. Visual analysis of the baseline phase, ASI phase, and ASI with parent training phase shows that all 3 fathers demonstrated an increase in the way they supported their child's playfulness; however, this change was not maintained. Children's playfulness fluctuated, reaching a peak after fathers received training, but none of the children maintained that change. Additional support by the therapist is required for fathers to learn and use new strategies to promote consistent change in child playfulness during play. Pilot data can be used to inform future studies. What This Article Adds: Occupation- and family-centered frameworks may be useful in guiding practice when working with families of children with ASD.